The Relationship of The Implementation of Warta DNAS O/153 with The Performance of Operations Officers - Masdini Agustriana, Titiek; Yuliana, Syafiyah (Journal of World Science, 2023)
The Babaranjang train accident at Penanggiran Station due to the negligence of operating officers playing cellphones caused the Operations Directors of PT.KAI will issue a ban on using cell phones during working hours to operating officers in Warta Dinas O/153. In the implementation of the O/153 official bulletin at Madiun Station, there are several problems, namely (1) limited coordination between the train travel control officer and the track inspector when there is a disturbance on the road because the walkie-talkie cannot reach, (2) the phenomenon of operational staff who is trying to break things, and (3) there are symptoms of stress, anxiety, or anxiety due to someone being away from a mobile phone, namely nomophobia (No Mobile Phone). Therefore, the author wants to examine the relationship between implementing official bulletins O/153 and the performance of operations officers at Madiun Station. Methods of data collection using questionnaires and data analysis using Spearman rank correlation. The research results obtained a correlation coefficient value of 0.432 and a significance value (2-tailed) of 0.024, less than 0.05. This means there is a relationship between the implementation of news service O/153 and the performance of operations officers at Madiun Station, with a moderately strong relationship and a positive direction.